ENGLISH LANGUAGE TEACHING IN BEGINNER CLASSES ANALYSIS OF THE UTILITY LEVEL OF EXERCISES IN TEXTBOOKS - Maftuna Khotamova Xoliqul qizi (Лучшие интеллектуальные исследования, 2023)
Annotation: The article determines how much the exercises in the textbooks for primary classroom learners are useful to enhance the formation and development of knowledge, skill, and habit in English according to the requirements of the Core Curriculum. The author develops the modern trends for textbook evaluation and criteria for analysis.